For this case we have:
Let k> 0:
To graph
the graph k units is moved up.
To graph
, the graph moves k units down.
Let h> 0:
To graph
, the graph moves h units to the right.
To graph
the graph moves h units to the left.
So, we have:
![y = f (x) = - \sqrt [3] {x}](https://img.qammunity.org/2020/formulas/mathematics/middle-school/16fct38enwpeaea40rp7orcg2f1xnun7rq.png)
Shifted 7 units up and 4 to the right means:
![k = 1\\h = 4](https://img.qammunity.org/2020/formulas/mathematics/middle-school/ehcpqdgxm0xgs0i5u6r1f1857nkmx6zeqn.png)
![y = f (x) = - \sqrt [3] {x-4} +7](https://img.qammunity.org/2020/formulas/mathematics/middle-school/vwutm0eq0ygzamlkxyeanpfzhv16d6zdwe.png)
Answer:
Option B